2005
DOI: 10.1161/01.cir.0000162472.52990.36
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Attenuation of Myocardial Vascular Endothelial Growth Factor Expression Is a Seminal Event in Diabetic Cardiomyopathy

Abstract: Background-Diabetic cardiomyopathy (DCM) is characterized by microvascular pathology and interstitial fibrosis, which leads to progressive heart failure; however, the pathogenesis of DCM remains uncertain. Methods and Results-Using the streptozotocin-induced diabetic rat model, we evaluated the natural course of DCM over a period of 1 year by serial echocardiography, Western blot analysis for vascular endothelial growth factor (VEGF), endothelial progenitor cell assays, myocardial blood flow measurements, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
134
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(150 citation statements)
references
References 53 publications
11
134
0
5
Order By: Relevance
“…[24][25][26] Disruption of the balance between myocyte growth and angiogenesis leads to contractile dysfunction and heart failure. VEGF plays a critical role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Disruption of the balance between myocyte growth and angiogenesis leads to contractile dysfunction and heart failure. VEGF plays a critical role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that capillary density in the heart is progressively decreased in Type 1 and Type 2 diabetic animal models, as well as in human diabetic patients (5,23,25,47,55). Decreased density of capillaries is due to loss of existing capillary network and attenuated regeneration of new capillaries.…”
mentioning
confidence: 99%
“…21 As diabetic patients with ischemic cardiomyopathy develop progressive congestive heart failure, however, local myocyte-secreted tissue VEGF levels begin to fall, further exacerbating the declining ventricular function seen in these patients. 11 In our rabbit model, with ligation of the proximal circumflex coronary artery, an infarction of the lateral wall of the left ventricle is produced. On the endocardial surface of the heart, this infarction is reliably centered at the base of the papillary muscles.…”
Section: Discussionmentioning
confidence: 99%
“…10 It is thought that local decreases in myocyte-secreted tissue VEGF contribute to as yet unspecified mechanisms of ischemic heart failure, especially in diabetes. 11 We have demonstrated earlier the ability of TERPLEXmediated plasmid VEGF gene therapy to ameliorate the detrimental effects of coronary occlusion on left ventricular function and to promote functional recovery following myocardial infarction. 12 Unregulated expression, however, limits the efficacy and safety of VEGF gene therapy within the myocardium.…”
Section: Introductionmentioning
confidence: 98%